2015
DOI: 10.24959/nphj.15.2029
|View full text |Cite
|
Sign up to set email alerts
|

The study of amino acid composition of sapropel by the capillary electrophoresis method

Abstract: (histidine, isoleucine, leucine, lysine, methionine, phenylalanine, threonine, tryptophan and valine) and a number of nonessential ones (alanine, arginine, glycine, proline and serine). Alanine, glycine, leucine, and isoleucine prevail in the mixture analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…The objects of the research comprised the sapropel extract from Prybych deposits (Volyn region, Ukraine), obtained by the method of cavitation [7], and excipients that were used during development of composition of the emulsifying base: Corn oil, emulsifier no. 1 (a mixture of fatty alcohols of the fraction С 16 -С 20 of the sodium salt of sulfoether of fatty alcohols), Cetearyl alcohol, and purified water [15][16][17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The objects of the research comprised the sapropel extract from Prybych deposits (Volyn region, Ukraine), obtained by the method of cavitation [7], and excipients that were used during development of composition of the emulsifying base: Corn oil, emulsifier no. 1 (a mixture of fatty alcohols of the fraction С 16 -С 20 of the sodium salt of sulfoether of fatty alcohols), Cetearyl alcohol, and purified water [15][16][17].…”
Section: Methodsmentioning
confidence: 99%
“…In these cases, the extraction of sapropel improves the environment due to the deepening of lake basins, and therefore, enhances the hydrological, hydrochemical, and biological regimen of lakes [5]. In sapropel, extracted from Prybych Lake, Volyn region, significant quantities of carboxylic acids [6], amino acids [7], micro-and macro-elements, and humic acids [8] were determined in our earlier investigations, that allows considering the natural raw material a perspective for the development of medicinal, cosmetic and veterinary products [5,9]. During the experimental studies, using cavitation method, we have improved the technology for preparation of the sapropel extract that provides a higher yield of humic and fulvic acids (above 20%) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Sapropelic therapeutic muds exhibit the anti-inflammatory and anti-allergic effect, protect the skin from the damaging effects of free radicals, slow down the aging processes, providing for skin a freshness, firmness, and elasticity, also improve cellular regeneration, moisturize, and increase elasticity and thickness of the keratoid layer of the epidermis. [4,6] The uses of native products and individual components of sapropels for many years have shown their effectiveness, accessibility, convenience, and safety.…”
Section: Original Articlementioning
confidence: 99%
“…A mong promising raw materials for preparation of medical, veterinary and cosmetic remedies are sapropel, which is a unique natural organic material, containing a large number of carboxylic, humic and amino acids, vitamins, micro-and macro-elements, and possessing a wide range of pharmacological effects, as well anti-inflammatory, reparative, antibacterial, and antioxidant. [1][2][3][4] In scientific literature, the term "sapropel" has been used mostly in a generic sense for describing organic-rich fine-grained sediments deposited in stagnant water. In respect to physical and chemical properties, sapropels are diverse materials with different content of organic substances and mineral nutrient concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental research has shown in the sapropel composition, extracted from Prybych Lake, the presence of significant amounts of carboxylic acids, amino acids, micro-and macroelements, humic acids (Nikolov 2014;Strus 2015a;Strus 2015b). The technology of sapropel extract production using the cavitation method was improved.…”
Section: Introductionmentioning
confidence: 99%